Relationship between Family Support and Personal Hygiene Behavior During Menstrual in Adolescents - Dini Mulyati; Suraya Putri; Raudhatul Jannah (GLOBAL HEALTH SCIENCE GROUP, 2025)
Personal hygiene behavior during menstruation affects adolescent reproductive health, including the risk of infection and cervical cancer. Family support, such as parents, especially mothers, plays a vital role in shaping adolescent personal hygiene behavior. This study aims to determine the relationship between family support and personal hygiene behavior during menstruation in junior high school adolescents in Banda Aceh City. This type of research is quantitative with a descriptive correlative method using a cross-sectional study design. The population of junior high school female adolescents in Banda Aceh City is 5,562 people. The sampling technique used the multistage random sampling method with a sample size of 249 female students. Data was collected by self-reporting using a questionnaire on family support and personal hygiene behavior during menstruation. Data were analyzed using chi-square. The results of the chi-square statistical test with a p-value of 0.039 showed a relationship between family support and personal hygiene behavior during menstruation in junior high school adolescents in Banda Aceh City.